Current Approaches to the Treatment of Traumatic Shock (Review) - D. A. Ostapchenko; A. I. Gutnikov; L. A. Davydova (Общая реаниматология, 2021)
The clinical manifestation of shock is characterized by systemic circulatory disturbances andblood ﬂow, hypoxic and metabolic disorders. The leading role in the pathogenesis of traumatic shock (the subtype of a hypovolemic shock), is assigned to the severity of the damaging eﬀect, the time interval suﬃcient for the development of a pathophysiological response, mismatch between body tissue perfusion and the metabolic requirements, and impaired aerobic oxidation in tissues. The use of a comprehensive multicomponent intensive care strategy matching the pathophysiological changes is a diﬃcult challenge for a critical care physician.The aim of the review is to demonstrate the speciﬁc features and sequence of events occurring in the body during the development of traumatic shock, the pattern of manifestations of clinical signs, and potential use of intensive therapy methods tailored to the pathophysiological responses in traumatic shock.Material. The information search was carried out in the PubMed and RSCI databases, among which 80 sources were ﬁnally selected, representing current therapeutic approaches, the results of scientiﬁc research and clinical guidelines related to the scope of this review.Results. The main stages of traumatic shock pathogenesis were reviewed. The basic patterns of cardiovascular and respiratory failure development were analyzed, the criteria of their severity were evaluated, and the complexity of the selection of intensive therapy was shown.Conclusion. Respiratory support, stabilization of cardiac and circulatory parameters and optimization of oxygen status are the most important components of treatment of patients with traumatic shock. Current methods of respiratory failure control allow to estimate promptly the severity of respiratory dysfunction, reveal the cause and correct existing disorders in an individualized way taking into account the better availability of mechanical ventilation. Replacement of circulating blood volume is aimed both at achieving hemodynamic eﬀect and restoring the concentration of sources of oxygen carriers and plasma pro- and anticoagulant factors. The earliest and most comprehensive intensive therapy can improve the prognosis and outcome in patients with traumatic shock.